2021
DOI: 10.47162/rjme.61.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Hormone treatment and UVB exposure influences on female mice regarding skin physiological parameters, biochemical parameters and organ histology

Abstract: Females require at a certain period of life the administration or supplementation of specific hormones (estrogen, progesterone), for various needs, such as: prevention of unwanted pregnancies, decreased menstrual bleeding, dysmenorrhea and pelvic pain in endometriosis, alleviation of symptoms associated with menopause, regulation of certain skin processes related to acne or aging and others. Also, hormones could act as oncogenes being known eloquent examples of estrogens labeled both as promoters of cell speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The most frequently associated diseases identified in the patients of the present study were high blood pressure, tumor conditions and autoimmune thyroiditis. Even if there are almost 100 years since few researchers suggested that could be an endocrine mechanism of otosclerosis, so far, no studies have been published in the English literature to demonstrate if there is a correlation between otosclerosis and autoimmune thyroiditis or different types of tumors [ 29 , 30 , 31 ]. These correlations should be well studied in the future, to be able to observe if exists an association between these pathologies and also an etiological pathway that could be interrupted by preventive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently associated diseases identified in the patients of the present study were high blood pressure, tumor conditions and autoimmune thyroiditis. Even if there are almost 100 years since few researchers suggested that could be an endocrine mechanism of otosclerosis, so far, no studies have been published in the English literature to demonstrate if there is a correlation between otosclerosis and autoimmune thyroiditis or different types of tumors [ 29 , 30 , 31 ]. These correlations should be well studied in the future, to be able to observe if exists an association between these pathologies and also an etiological pathway that could be interrupted by preventive therapies.…”
Section: Discussionmentioning
confidence: 99%